Misperceptions of the Government's Authority to Provide Legal Aid in Review of Hierarch Legislation - Hanum, Roro; Syakir, Muhammad; Lidya Putri, Nyimas; Irawan, Hendra; Permana Putra, Aldi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
The misperception of authority within the Metro City Regional Government has led to inconsistencies between Law Number 16 of 2011 and Metro City Regional Regulation Number 16 of 2013 regarding the implementation of legal aid. This misperception has also created a legal vacuum, as the Ministry of Home Affairs Regulation mandates the mandatory authority of the Regional Government, which is ignored in providing legal aid to the Minister, Regional Head/Deputy Regional Head, CPNS/PNS, while the Regional Government focuses more on regulations regarding legal aid for the poor. This research uses a qualitative approach to gain a deeper understanding of the law and regulation formation process. The data sources were obtained directly from the Metro City Regional Government, specifically from the Legal Section handling legal aid, as well as through social media, news websites, and government websites related to the archives of the formation of Regional Regulation Number 6 of 2013. The data analysis adopts Hans Kelsen's theory in General Theory of Law and State and the theory of the hierarchy of laws and regulations. Given the misperception that causes inconsistencies and a legal vacuum, a review of the existing regulatory hierarchy system is needed. To address this, it is necessary to review the local regulation to align it with Law Number 16 of 2011, through mechanisms such as judicial review or revisions by the local legislative body, although until now, there has been no follow-up from the Metro City Regional Government or the Provincial Government.